(untitled) (Research, Society and Development, 2021)
Severe Acute Respiratory Syndromes (SARS) can be defined by the presence of fever, cough (or sore throat) and dyspnoea, or reduction in O2 saturation. Although they have many etiologies, during the 2020 pandemic occurred a significant increase in the reported cases resulting from infections by SARS-CoV-2. The present study aims to describe the clinical, epidemiological and laboratory data of patients admitted to the University Hospital of the Federal University of Vale do São Francisco with suspected SARS due to COVID-19 or unspecified. This is a retrospective, observational cross-sectional study, with a sample of 72 individuals, admitted between March and July 2020. Data were collected from electronic medical records. For data analysis, simple and relative frequencies were calculated and statistical analysis were performed using SPSS. Most individuals were male and had an average age of approximately 57 years. Regarding comorbidity 86.11% had at least one. The most prevalent being hypertension, advanced age and metabolic disorders. Fever, reduced O2 saturation and dyspnoea were the most common symptoms among the 47 patients infected with SARS-CoV-2. High levels of TGO, D-dimer and ferritin, as well as a reduction in the rates of albumin and hemoglobin were the most common laboratory alterations. Furthermore, 74.5% required mechanical ventilation, and the major outcome was death. The data described are able to help clinical practice, as they show the most frequent findings observed in individuals with SARS.